PENGARUH PARTISIPASI PENYUSUNAN ANGGARAN TERHADAP KINERJA MANAJERIAL DENGAN KOMITMEN ORGANISASI DAN GAYA KEPEMIMPINAN SEBAGAI VARIABEL MODERATING PADA PT PUPUK SRIWIDJAJA PALEMBANG - Fertika Andriana; Ermadiani Ermadiani; Yusnaini Yusnaini (Department of Accounting, Faculty of Economics, Universitas Sriwijaya, 2013)
The study modified from Muhlis et al (2010) on the influence of participation of budgeting on the performance of regional government apparatus with organizational culture and organizational commitment as Moderator. The object in this research is PT Pupuk Sriwidjaja Palembang. Data is processed using SPSS. From the results of analysis can be concluded that there is a positive influence and relation between participation of budget to managerial performance, there is no influence of organizational commitment to the participation relationship of budget preparation and Managerial performance. There is a negative and significant influence over the leadership style of the relationship between the participation of budget and managerial performance, which means leadership style weakens the influence of budget-making participation in managerial performance.